Omalizumab for the treatment of chronic spontaneous urticaria: a systematic review - Rao, Nishitha Gopal; Jing, Hai Xia; Kabir, Ahmed Raihan; Surthi, Rohit (International Journal of Research in Dermatology, 2021)
Chronic spontaneous urticaria (CSU) is a mast cell-driven skin disease characterized by the recurrence of transient wheals, angioedema or both lasting for more than 6 weeks duration. Omalizumab is a newer humanized anti IgE immunoglobulin along with many new antibody treatments has shown beneficial effect in treatment of chronic spontaneous urticaria. Although many randomized clinical trials have been conducted, as of now, the effectiveness of omalizumab in the real world management of CSU is largely unknown. A systematic review of all studies should be done. The objective was to study the efficacy and safety of different doses of omalizumab in the treatment of chronic spontaneous urticaria which was refractory to treatment with H1 antihistamines. Suitable studies were recognized after searching Wiley online library, PubMed, Google scholar, NEJM/NEJ dermatology, JAAD, JACI, clinicaltrials.gov. Only randomized, double-blind, placebo-controlled clinical trials with omalizumab versus antihistamine or leukotriene antagonists as placebo were involved in this study. 10 randomized, placebo-controlled studies were involved with 1692 patients with CSU. Patients treated with omalizumab (75-600 mg every 4 weeks) had reduced UAS7 score, improved QoL (quality of life), reduced WISS, when compared to the placebo group. The effects of omalizumab were found to be dose dependent, with maximum reduction in UAS7 at a dose of 300 mg when given at an interval of 4 weeks’ duration. The incidences of adverse events were almost similar in both control and placebo groups and across various dose ranges. The best effect in reduction of clinical symptoms and QoL in CSU patients was found at a dose of 300 mg subcutaneous injection once a month of omalizumab for 12 to 24 weeks. Omalizumab was found to reduce the clinical symptoms and signs in patients with CSU who were symptomatic despite treatment with upscaling dose of H1 antihistamines.